Availability, accessibility and delivery to patients of the 28 orphan medicines approved by the European Medicine Agency for hereditary metabolic diseases in the MetabERN network - Heard, Jean-Michel; Kölker, Stefan (Orphanet journal of rare diseases, 2020)
The European Medicine Agency granted marketing approval to 164 orphan medicinal products for rare diseases, among which 28 products intended for the treatment of hereditary metabolic diseases. Taking advantage of its privileged connection with 69 healthcare centres of excellence in this field, MetabERN, the European Reference Network for hereditary metabolic diseases, performed a survey asking health care providers from 18 European countries whether these products are available on the market, reimbursed and therefore accessible for prescription, and actually delivered in their centre.
Gesehen am 07.04.2020